Factors Affecting Construction Speed of Industrialized Building System in Malaysia - Mohammed Al-Aghbari, Wa'el Abdulmoghni (2005)
Malaysia is presently taking a serious look at IBS as an answer to the housing shortage problem. There are many advantages using the IBS according to a report published by the Malaysian Ministry for Local Government and Housing. The main advantages are the speed of construction, quality and price. All of these are required to meet the large demand for housing. This thesis presents the speed of construction methods which are the conventional system, cast-in-situ method, composite methods, and the Industrialized Building System; including the factors that affect the speed of IBS and the factors causing delay in building construction projects.The data were collected through mailing questionnaires distribution. The questionnaire took into consideration the factors on sample size, time, speed and causes of delay. The questionnaire was distributed to four hundred and fifty respondents among developers, government boards, main contractors, consultants and manufactures who were concerned with the building systems of construction projects in Malaysia. The return was seventy eight respondents. The statistical descriptive analysis was used to identify whether the respondents have the necessary sufficient qualification to respond correctly to the questionnaire. However, spearman correlation analysis was used to find out the significant scenario of the construction method. The Logit linear analysis was used to choose between the IBS and the conventional methods. In addition, it is used to test these hypotheses since it is a useful mean of both summarizing the results of data analysis and comparing the effects of different speed factors on the probability to choose the construction method. The results have been analyzed to rank the factors affecting the speed of IBS and the factors causing the delay of building construction projects. As a result from the analysis, it was observed that the full-prefabricated method was the fastest construction method compared to the other methods. Moreover, the high productivity of structural elements (in-situ or off-situ) is the most important factor that had an effect on the speed of IBS. The study also revealed many factors causing delay in building construction projects in Malaysia. These factors could be financial from both the contractors and the owners' side. Poor management is also an important factor causing delay. However, a ver) important factor for the delay could be from the consultant's side where the supervision is conducted at a very late stage during the execution of the projeci and the incompetence in giving timely instructions. Finally, the most importan' external factor causing delay is the lack of materials in the market. The result of the study is that there should be continuous improvement of the IBS which focus mainly on innovating techniques to improve the productivity The financial support as well as technical support is very necessary and urgent for building construction projects.